3D printing of polylactic acid/poly ethylene glycol/hydroxyapatite porous bone scaffolds and their biocompatibility - FAN Ze-wen; ZHAO Xin-yu; QIU Shuai; WANG Yan; GUO Jing; QUAN Hui-xin; XU Lan-juan (Cailiao gongcheng, 2021)
Polylactic acid (PLA) is a widely used biopolymer material. However, there are disadvantages such as poor toughness, poor hydrophilicity, and poor biological activity in the application process. It was modified with polyethylene glycol (PEG) and hydroxyapatite (HA).3D printing filaments of PLA/PEG/HA with different mass ratios were prepared by melt blending. And by analyzing the mechanical properties, crystallization properties, thermal properties, rheological properties of PLA/PEG/HA filaments, the more suitable filaments for fused deposition modeling of 3D printing (FDM) were screened, and then the high precision mechanical samples and bioporous scaffolds with good biocompatibility, cell value-added and differentiation were 3D printed. The results show that the addition of PEG improves the toughness of PLA and lowers the melting point of PLA. The addition of HA increases the elastic modulus and cold crystallization temperature of PLA/PEG/HA composites, and HA can also improve the flowability of PLA/PEG/HA composites. SEM and fluorescent labeling results show that the porous scaffold has good biocompatibility. The successful cultivation of bioscaffolds in vitro cells provides potential for further exploration of bioporous scaffolds in animals, biomedicine, and customized applications.